First Molecular Characterization and Haplotype Analysis of Ligula pavlovskii (Cestoda: Diphyllobothriidae) from Podiceps cristatus in Türkiye: A Novel Geographic Record with Phylogenetic Insights - Ozturk, Mehmet; Nacar, Can; Umur, Sinasi (Springer, 2025)
Ligulosis is an important parasitic disease of freshwater fish, causing serious economic losses in the fisheries industry. In this study, we report the distribution of Ligula pavlovskii in avian definitive hosts in T & uuml;rkiye and the first genetically confirmed presence of this species in Podiceps cristatus (great crested grebe). To achieve this, the mitochondrial cox1 gene region was used for molecular characterization and phylogenetic assessment. The population structure was evaluated by applying haplotype diversity, DNA polymorphism, and neutrality tests to the sequences obtained. Visual representations of Ligula isolate from T & uuml;rkiye were created using alluvial diagrams (molecularly identified) and sunburst diagrams (morphologically identified). Although only the cox1 marker was used in this study, the results provide reliable molecular support for species identification. The data obtained provide important contributions to the literature on the distribution and genetic diversity of Ligula spp. in T & uuml;rkiye.
Keywords: Birds; Cox; Ligula Pavlovskii; Podiceps Cristatus; T & Uuml; Rkiye